«Da che parte sta il corpo rispetto allo spirito?» - Randi, Elena (Mimesis Journal, 2015)
This paper starts from the idea that the relationship between body and spirit – although shaped from the most different perspectives – is the central theme in many writings of Umberto Artioli’s. Artioli very often chose to investigate the authors and currents in which this theoretical theme was dealt with, and then he often fixed his attention on it, rather than choosing other issues. Elena Randi demonstrates her thesis examining Artioli’s investigations on a number of subjects: from D’Annunzio to Pirandello, from Artaud to Fuchs, from Carmelo Bene to Futurism.